Studies on the achene morphology of Turkish species of Scorzonera L. (Asteraceae) using light and scanning electron microscopy - Coşkunçelebi, Kamil; Makbul, Serdar; Okur, Seda (Phytotaxa, 2016)
Macro- and micromorphological features of achenes belonging to 59 taxa from Turkey were observed via light and scanning electron microscopy. The findings agree with the traditional subdivision of Scorzonera into S. subg. Scorzonera, S. subg. Podospermum and S. subg. Pseudopodospermum. Members of S. subg. Podospermum were distinguished by achenes with a distinct carpopodium and horizontally striped epidermal cell surface; members of S. subg. Pseudopodospermum were distinguished by achenes with a conspicuous carpopodium and often ruminate and sometimes rugose-granulate or smooth epidermal surface, and members of Scorzonera s.str were distinguished by achenes without a carpopodium and with various combinations of surface patterns. The results also showed that the length, pubescence and surface pattern of achenes, as well as the carpopodium and anticlinal and periclinal walls of the epidermal cells are valuable for delimiting the examined species within the genus.